EUROPEAN PRACTICE OF IMPLEMENTING BARRIERABILITY: INTERNATIONAL EXPERIENCE FOR UKRAINE (Regional aspects of productive forces development of Ukraine, 2026)
Introduction. The article examines the key principles and mechanisms of forming an inclusive environment in the European Union countries and analyzes the possibilities of their application in the Ukrainian context. Based on the study of European regulatory acts, policy documents, and successful case studies of individual countries, the EU's systemic approach to ensuring accessibility is highlighted. This approach combines legislative regulation, financial support, and public monitoring.Purpose. The purpose of the article is to analyze and summarize the European experience in forming and implementing accessibility policy to identify practical lessons, adapted recommendations, and specific mechanisms for the effective implementation of similar practices in Ukraine, taking into account current challenges.Research methods are based on a comprehensive approach. The main method is system analysis, which allows considering the European experience as an integral structure. It is complemented by comparative legal analysis to compare European norms with Ukrainian legislation and document analysis. The obtained data are generalized and synthesized to model mechanisms for implementing accessibility adapted for Ukraine, considering the challenges of post-war reconstruction.Results. The modern world is moving toward inclusivity, where creating an accessible environment for all citizens is not just a requirement of our time but an essential component of social justice and sustainable development. Ukraine, which is actively pursuing European integration, faces numerous challenges in ensuring barrier-free access for people with disabilities and individuals with limited mobility. In this context, European experience in implementing accessibility principles is particularly valuable, offering ready-made solutions and effective mechanisms that could be beneficial for Ukrainian realities.  The purpose of this study is to comprehensively analyze European approaches to creating an accessible environment, particularly in the areas of legal regulation, infrastructure planning, digital inclusion, and social integration. Special attention is paid to key European initiatives such as the European Accessibility Act, as well as successful national practices of individual EU countries in universal design, adaptation of public spaces, and transportation infrastructure.  The research demonstrates that European experience in accessibility can serve as an effective tool for accelerating the development of an inclusive society in Ukraine. Successful implementation of European approaches requires comprehensive changes—from improving legislation to transforming public awareness—which will allow Ukraine not only to adopt the best international practices but also to develop its own effective model of ensuring accessibility for all citizens.Keywords: accessibility, inclusion, European Union, universal design, people with disabilities, urban design.Formulas: 0, fig.2: 0, tabl.: 0, bibl.: 4.